“Sorry for laughing, but it’s scary”: humor and silence in discussions of Colorectal Cancer with Urban American Indians - Buchwald, Dedra S; Bassett, Deborah R; Van Dyke, Emily R; Harris, Raymond M; Hanson, Jessica D; Tu, Shin-Ping (BMC Cancer, 2023)
BackgroundGiven high rates of cancer mortality in Native communities, we examined how urban American Indian and Alaska Native elders talk about colorectal cancer (CRC) and CRC screening.MethodsWe conducted seven focus groups with a total of 46 participants in two urban clinics in the Pacific Northwest to assess participant awareness, perceptions, and concerns about CRC and CRC screening. Using speech codes theory, we identified norms that govern when and how to talk about CRC in this population.ResultsOur analyses revealed that male participants often avoided screening because they perceived it as emasculating, whereas women often avoided screening because of embarrassment and past trauma resulting from sexual abuse. Both men and women used humor to mitigate the threatening nature of discussions about CRC and CRC screening.ConclusionsWe offer our analytic results to assist others in developing culturally appropriate interventions to promote CRC screening among American Indians and Alaska Natives.